Approaches to school management: an approximation from the latin american perspective - Naranjo Mayorga, Nelson (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The Management itself is the set of integrated actions for achieving of a purpose to a certain period. In this sense, it is the main action of management, being an intermediate link between the planning and the specific objectives which are achieved. In general, the administration of educational institutions will be the following among others actions: administrative, managerial, personnel policy, financial (budget), planning etc.